2014
DOI: 10.1620/tjem.234.169
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Body Mass Index and Breast Cancer Risk or Estrogen Receptor Status in Okinawan Women

Abstract: Dietary changes resulting from the post-World War II occupation of Okinawa by the US military have been largely deleterious, resulting in a marked increase of obesity among Okinawan residents. In this study, we examined the association between BMI and the risk of developing breast cancer according to the menstruation status and age, and the correlation between BMI and expression of estrogen receptor (ER). Breast cancer cases were 3,431 females without any personal or family history of breast cancer. Control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…As previous studies indicated that increased BMI was associated with the increased risk of BC in Okinawa (Tamaki et al 2014), we wanted to determine whether there was an association between HSP70 and obesity. Therefore we divided patients into two subgroups, according to BMI above (obese) or below (non-obese) 30 kg/m 2 (World Health Organization 2011).…”
Section: Resultsmentioning
confidence: 99%
“…As previous studies indicated that increased BMI was associated with the increased risk of BC in Okinawa (Tamaki et al 2014), we wanted to determine whether there was an association between HSP70 and obesity. Therefore we divided patients into two subgroups, according to BMI above (obese) or below (non-obese) 30 kg/m 2 (World Health Organization 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of the US lifestyle and diet to people of Okinawa is generally considered the simplest and most plausible explanation of the clearly documented loss of longevity advantage among younger generations of Okinawan people (Todoriki et al 2004;Willcox 2005;Tamaki et al 2013). We reported on the correlation between BMI and breast cancer risk for Okinawan people and in particular increased risks associated with the marked increment of BMI since US military occupation in our previous study (Tamaki et al 2014). Results of this study demonstrated that the Okinawan women who were overweight and/or obese during premenopausal and postmenopausal ages had a statistically significant higher risk of breast cancer development compared to those with non-overweight and/or obese women (Tamaki et al 2014).…”
Section: Lifestylementioning
confidence: 63%
“…Results of this study demonstrated that the Okinawan women who were overweight and/or obese during premenopausal and postmenopausal ages had a statistically significant higher risk of breast cancer development compared to those with non-overweight and/or obese women (Tamaki et al 2014). The Okinawan people have adjusted to low calorie environment for more than a millennium in a rather isolated island environment (Tamaki et al 2014). Thus, this increment of breast cancer development in Okinawan women following World War II might be explained by the introduction of an US style diet as a result of the US military occupation, oversaturation by lipids and cholesterol of the liver clearance system of estrogen in Okinawan overweight women, expose their system to much endogenous estrogen (Tamaki et al 2014).…”
Section: Lifestylementioning
confidence: 78%
See 2 more Smart Citations